Association Study between Novel CYP26 Polymorphisms and the Risk of Betel Quid-Related Malignant Oral Disorders. (9th March 2015) - Wu, Shyh-Jong; Chen, Yun-Ju; Shieh, Tien-Yu; Chen, Chun-Ming; Wang, Yen-Yun; Lee, Kun-Tsung; Lin, Yueh-Ming; Chien, Pei-Hsuan; Chen, Ping-Ho
Abstract : BQ chewing may produce significant amounts of reactive oxygen species (ROS), resulting in oral mucosa damage, and ROS may be metabolized by CYP26 families. Because the CYP26 polymorphisms associated with malignant oral disorders are not well known, we conducted an association study on the associations between the single nucleotide polymorphisms (SNP) of CYP26 families and the risks of malignant oral disorders. BQ chewers with the CYP26A1 rs4411227 C/C+C/G genotype and C allele showed an increased risk of oral and pharyngeal cancer (adjusted odds ratio (aOR) = 2.30 and 1.93, respectively). The CYP26B1 rs3768647 G allele may be associated with oral and pharyngeal cancer (aOR = 3.12) and OPMDs (aOR = 2.23). Subjects with the rs9309462 CT genotype and C allele had an increased risk of oral and pharyngeal cancer (aOR = 9.24 and 8.86, respectively) and OPMDs (aOR = 8.17 and 7.87, respectively). The analysis of joint effects between the CYP26A1 rs4411227 and CYP26B1 rs3768647/rs9309462 polymorphisms revealed statistical significance (aOR = 29.91 and 10.03, respectively). Additionally, we observed a significant mRNA expression of CY26A1 and CYP26B1 in cancerous tissues compared with adjacent noncancerous tissues. Our findings suggest that novel CYP26 polymorphisms are associated with an increased risk of malignant oral disorders, particularly among BQ chewers.